Face naming and retrieval inhibition in old and very old age (2014)
Background/Study Context: Aging has traditionally been related to impairments in proper name retrieval. This study analyzed the possible role of the Inhibitory Deficit Hypothesis in explaining face naming impairments during aging. The dynamics of inhibition have been thoroughly studied by the retrieval-practice paradigm (Anderson, Bjork, & Bjork, 1994, Journal of Experimental Psychology: Learning, Memory, and Cognition, 20, 1063-1087) and its aftereffect, the retrieval-induced forgetting effect.Methods: A version of the retrieval-practice paradigm was employed: younger-old (YO; mean age = 66.40, SD = 3.94) and older-old (OO; mean age = 80.94, SD = 4.53) adults were asked to repeatedly name faces of categorically related famous people.Results: Retrieval-induced forgetting for names was observed in the YO group but not in the OO group.Conclusion: These findings indicate that whereas the YO adults had enough resources to inhibit intrusive names, OO adults were not able to suppress competing names, supporting the proposal of the Inhibitory Deficit Hypothesis at older ages. © 2015, Taylor & Francis Group, LLC.